(untitled) (Medical Forum Monthly, 2020)
Objective: To evaluate the incidence of meconium-stained amniotic fluid (MSAF) and associated characteristics in women with term deliveries. Study Design: A case–control study Place and Duration of Study: This study was conducted at the Obstetrics and Gynecology, Department unit 2, Kausar hospital Mother & Child Health Care Center, Khairpur, and Khairpur Medical College, Khairpur Mirs between January to August, 2020 for a duration of eight months. Materials and Methods: During the study period, a total of 73 cases with meconium stained amniotic fluid were recruited and 73 healthy subjects with clear amniotic fluid acted as control. Women with breech presentation, congenital abnormality, twin births, stillbirth or preterm or late-term cases were excluded from the study. All socio demographic and obstetrical data of mothers was feeded into an electronic predefined questionnaire via face to face interviews. Women in the case group were divided into 3 grades and sub-stratified according to their sociodemographic and obstetrical characteristics. Data was analyzed using SPSS version 26. Results: There were seventy-three cases of MSAF during the study period. The mean age and standard deviation of women in the case (MSAF) group was 36.06 years with the range 26 – 42 years. The mean maternal age was significantly lower in the control group (p-value < 0.00001). There were 16 women with Grade I MSAF, 40 women with Grade II, and 17 women with Grade III MSAF. Prolonged labour of greater than 12 hours was more frequently observed in the MSAF group compared to the control healthy subjects with clear amniotic fluid. Out of the 73 women with MSAF, about 59 participants delivered via caesarean section while the rest 11 had spontaneous vaginal delivery. In contrast, a relatively lower number of women in the control group delivered via C-section. Conclusion: Increased gestational age, delayed or obstructed labor, induced-labor, and cesarean section may be associated with increased risk of development of meconium-stained amniotic fluid. MSAF should be carefully investigated and a mother with MSAF and the fetus during delivery should be regularly and vigilantly monitored.